UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA DENGAN METODE COOPERATIVE SCRIPT - Ika Septi Hidayati (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2020)
The purpose of this study was to determine the appropriate application of the cooperative script method in order to increase the learning interest of the fifth grade students of SD Negeri Prembulan. The results of this study indicate that: (1) In general, the application of the appropriate cooperative script method is effective in increasing interest in learning mathematics, (2) Increasing interest in learning mathematics for fifth grade students of SD Prembulan in pre-cycle by 62.07 in cycle I of 76, 31 in cycle II amounted to 85.39.